Effectiveness To Complete Disaster Information System In Bali Province - Cici Noer Alfiyani; Ayu Berliani; Nadila Watora; Luh Putu Vera Astri (Universitas Sultan Ageng Tirtayasa, 2022)
The digitalization process in the field of disaster management is very important to be carried out to minimize the occurrence of a disaster. This study aims to find out how the digitalization process is being carried out in the OPD of the Bali Province Regional Management Agency in disaster management. The sampling technique in this study used purposive sampling, namely the respondents in the field of Pusdalops BPBD Bali Province, their leaders and staff who served in the data center and operations regarding disaster as many as 26 people. Data collection techniques using interviews, observation, documentation and literature review. The results of this study indicate that the digitalization process is very important in providing information to the public to reduce the risk of a disaster occurring. This research has implications for local governments to follow the digitization process more so that information can be conveyed properly to the wider community